Transcriptional Responses of HPG-Axis Genes and Hepatic vtg to 11-Ketotestosterone in Previtellogenic Sterlet (Acipenser ruthenus) - Wei Wang; Ying Dong; Tian Dong; Linan Gao; Hua Zhu; Xuetong Bi; Hongxia Hu (Fishes, 2026)
11-ketotestosterone (11-KT) has previously been shown to promote previtellogenic ovarian development and vitellogenin-related hepatic responses in sterlet (Acipenser ruthenus), but the endocrine genes involved in this process remain unclear. In this study, previtellogenic female sterlets were implanted with slow-release 11-KT strips at 5 or 25 mg/kg for 30 days, and transcriptional responses of HPG-axis-related genes, including GnRH paralogs, gonadotropins, and gonadotropin receptors, were examined in the brain-pituitary complex, liver, and ovary. In the brain-pituitary complex, 11-KT increased fsh expression in the 25 mg/kg group and upregulated fshr in both treatment groups, whereas gnrh paralogs showed limited responses. In the liver, most GnRH- and gonadotropin-related genes were not significantly altered, suggesting that hepatic expression of upstream reproductive-axis genes was not a major in vivo target of 11-KT feedback. The ovary exhibited the strongest response, with increased gnrh2 and fsh expression and reduced gnrh3, fshr, and lhr expression, especially at the higher dose. To further examine receptor-related regulation of hepatic vtg expression, liver tissue was incubated in vitro with 11-KT alone or in combination with the androgen receptor antagonist flutamide or the estrogen receptor antagonist fulvestrant. Flutamide did not abolish 11-KT-induced vtg expression, whereas high-dose fulvestrant reduced both era and vtg expression relative to 11-KT treatment alone. Overall, 11-KT elicited tissue-specific transcriptional responses in HPG-axis-related genes, particularly involving ovarian gnrh2, fsh, fshr, and lhr. The differential antagonist responses observed in liver explants provide in vitro evidence consistent with the involvement of ER-associated signaling in hepatic vtg expression, but do not establish direct receptor-mediated regulation.

Harvesting reed (Phragmites australis) for wetland nitrogen removal: Productivity, microbial communities, and underlying mechanisms - Junli Wang; Yucui Bi; Zishi Fu; Hongxia Qiao; Fuxing Liu (Bioresource Technology, 2026)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Enhancing total nitrogen removal in constructed wetlands: A Comparative study of iron ore and biochar amendments - Yucui Bi; Fuxing Liu; Zishi Fu; Hongxia Qiao; Junli Wang (Journal of Environmental Management, 2024)

Linking rhizospheric microbiota and metabolite interactions with harvested aboveground carbon and soil carbon of lakeshore reed wetlands in a subtropical region - Junli Wang; Zishi Fu; Hongxia Qiao; Fuxing Liu; Yucui Bi (Plant and Soil, 2024)

Effects of substrate improvement on winter nitrogen removal in riparian reed (Phragmites australis) wetlands: rhizospheric crosstalk between plants and microbes - Junli Wang; Zishi Fu; Fuxing Liu; Hongxia Qiao; Yucui Bi (Environmental Science and Pollution Research, 2023)

BLE-based floor positioning method for multi-level atrium spatial environments - Hongxia Qi; Yunjia Wang; Jingxue Bi; Hongji Cao; Shenglei Xu; Hui Liu (Acta Geodaetica et Geophysica, 2021)

Fast floor identification method based on confidence interval of Wi-Fi signals - Hongxia Qi; Yunjia Wang; Jingxue Bi; Hongji Cao; Minghao Si (Acta Geodaetica et Geophysica, 2019)

miR-1260b promotes cell migration and invasion of hepatocellular carcinoma by targeting the regulator of G-protein signaling 22 - Xiaoying Li; Hongxia Song; Zhirong Liu; Yunsheng Bi (Biotechnology Letters, 2018)